Nós, as mulheres/nós femininas: rupturas e multiplicidades em as doze cores do vermelho, de Helena Parente Cunha - Martiniano, Graziela Sousa Lima (2019)
The complex literary representation constructed by Helena Parente Cunha in The Twelve Colors of the Red (1989) provoked the search for an analysis and provided a rereading on the sexist values reproduced in our society. The reader, as he dwells upon the reading of his novel, has his critical sense sharpened, with a questioning view of these still extant standards. In view of this, this research constitutes a theoretical study, having as an analytical object the persons created by the Bahian writer. The purpose of this choice is to understand how the characters demystify the female subject represented in the historical-socio-political-literary process by the male imaginary, instituted through mechanisms of power; and how these representations interfere in the identity construction of this subject. In this context, the discussion assumes the need not only to discuss the process of constructing the feminine identity, through representations in literary writing, but also to problematize how these cultural practices were responsible for reserving to women a static social mold. To carry out this work, a bibliographic corpus study was done in the context of the studies that discuss the condition, the feminine identities and representations. Initially, the peculiarities of the author’s production were identified, in order to point out their prominence and their importance in the scope of Brazilian literature. Next, theories about culture, identities and representations in literary studies are discussed and, from this point on, an analysis of this feminine subject of multiple identity present in the novel was made, trying to understand the feminine identity as a becoming. The research contributes to widen the existing debates about the work of the writer and proposes a questioning dialogue around the established truths that reserved to women pre-determined places in society.